2004
DOI: 10.3139/217.1826
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Long-term Creep Behavior of Plastics Using the Short-term Creep Test

Abstract: The creep performance of plastics is one of the main criteria for a variety of applications which requires a strict dimensional stability, including electrical/electronic parts and various automotive applications. However, obtaining or generating accurate creep data is very difficult for both resin suppliers and product designers because the creep property is time dependent, which means it takes over several weeks or even a year of time span. Hence a faster and more reliable method predicting creep behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Aerospace 2022, 9, 124 9 of 13 were considered. According to the open literature, these tests are an easy, fast and reliable method to predict long-term behaviour [23][24][25]. On the other hand, it is also reported that an initial stage occurs in which the stress decreases considerably in relation to the remaining time [26][27][28], and this evidence is also observed in the present study for all compressive strains analysed.…”
Section: Resultssupporting
confidence: 86%
“…Aerospace 2022, 9, 124 9 of 13 were considered. According to the open literature, these tests are an easy, fast and reliable method to predict long-term behaviour [23][24][25]. On the other hand, it is also reported that an initial stage occurs in which the stress decreases considerably in relation to the remaining time [26][27][28], and this evidence is also observed in the present study for all compressive strains analysed.…”
Section: Resultssupporting
confidence: 86%
“…In both cases, the data were analyzed according to the respective ASTM standards. On the other hand, and as reported in the open literature [ 26 , 27 , 28 ], these short-term tests reveal to be an easy, fast, and reliable method to predict long-term behavior. In fact, due to the main costs incurred with long-term test programs, in addition to the fact that long periods between the development of new or improved materials and their applications are not allowed, it is highly desirable that the design data could be obtained by extrapolating the results obtained by short-term tests.…”
Section: Methodssupporting
confidence: 64%
“…In general, the stress decreased over time to one value expected to be constant, but in the present work, this constant bending stress was not achieved because it focuses on short-term tests. These tests represent an easy, fast, and reliable method to predict long-term behavior [ 26 , 27 , 28 ]. Another similarity with the open literature is the existence of an initial stage, in which the stress decreases considerably with the remaining time [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The numerical outcomes were compared with the experimental and simulation results and found in close approximation with the real-time environment. Lim et al [ 33 ] presented a method for prediction of long term creep behavior using a short term creep experimental data. The experiments were performed on ABS, PC-ABS, and long fiber reinforced thermoplastics (LFT).…”
Section: Introductionmentioning
confidence: 99%